OP0128 The phenotype of axial psoriatic arthritis: is it dependent on hla-b27 status?. (12th June 2018) - Coates, L.; Alonso, E.; Baraliakos, X.; Blanco Garcia, F.; Braun, J.; Chandran, V.; Fernandez-Sueiro, J.L.; FitzGerald, O.; Gallagher, P.; Gladman, D.; Gubar, E.; Korotaeva, T.; et al.
Abstract : Background: Up to 50% of patients with psoriatic arthritis (PsA) have associated spinal involvement similar to ankylosing spondylitis (AS). HLA-B27 positivity is lower in PsA compared to other SpA which may affect the disease phenotype. Objectives: Our aim was to compare axial phenotype in PsA patients with and without HLA-B27 with AS patients. Methods: A large international collaboration collected BASDAI, CRP, HLA-B27 status and sacroiliac joints (SIJ) and spine radiographs. These were read centrally by two blinded readers using consensus on the modified New York criteria, mSASSS and PASRI. AP spine radiographs were examined for symmetry (score difference ≥2 between sides) and morphology of syndesmophytes (typical marginal vs atypical chunky/non-marginal) were compared. Results: Eight sites contributed 244 (25% HLA-B27+) PsA patients and 198 (75% HLA-B27+) AS patients. Mean BASDAI, mSASSS and PASRI were higher in AS. When categorised by diagnosis and HLA-B27 there were significant differences for age, sex, disease duration, mSASSS, PASRI and syndesmophyte symmetry. Regression analysis, with mSASSS and PASRI as dependent variables revealed significant associations with age, sex, duration of disease, and group (HLA-B27 and diagnosis). Binary multivariate logistic regression was used to investigate associations of age, sex, HLA-B27 status, diagnosis (PsA v AS) and concomitant diabetes with radiographic features. Sacroiliac symmetry showed no significant associations, whilst syndesmophyte symmetry was associated with increasing age and HLA-B27 positivity. Typical marginal syndesmophytes were associated with age, HLA-B27 status and disease duration: in the cervical spine significant associations with age, sex and HLA-B27 status; in the lumbar spine with age, HLA-B27 and diagnosis. Atypical chunky syndesmophytes were associated only with increasing age and male sex. Conclusions: This analysis suggests less difference in radiographic phenotype between AS and axial PsA than previously thought. HLA-B27 negative PsA patients have less severe disease as measured by mSASSS and PASRI with less typical marginal syndesmophytes and symmetry, whilst HLA-B27 positive PsA appears similar to AS. Disclosure of Interest: None declared